2013
DOI: 10.4236/jep.2013.44a007
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Volatile Organic Compounds-Degrading <i>Bacillus</i> Strains from Loess

Abstract: Volatile organic compounds (VOCs) are harmful to human health and the environment. Recently, loess (Hwangtoh) was used as an eco-friendly interior paint formulation in Korea. It is used even more commonly as a filter carrier to remove VOCs. In this study, we isolated Bacillus strains from a loess filter. The strains that were tolerant to VOCs were labeled according to the series VOC01 to VOC35. Four strains-VOC03, VOC11, VOC18, and VOC30-were investigated for their ability to degrade cyclohexane and toluene. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A low number of cyclohexane-degrading strains are reported in literature, and the research is mainly focused on the biochemical characterization without identification of the genes involved in the degradation process of cyclohexane (Anderson et al 1980;Trower et al 1985;Lee and Cho 2008;Lee et al 2013;Opere et al 2013). Contrarily, degradation pathways of cyclohexanol and cyclohexanone were described in detail for the bacterial strains Acinetobacter sp.…”
Section: Identification Of a Novel Cyclohexane Monooxygenasementioning
confidence: 98%
“…A low number of cyclohexane-degrading strains are reported in literature, and the research is mainly focused on the biochemical characterization without identification of the genes involved in the degradation process of cyclohexane (Anderson et al 1980;Trower et al 1985;Lee and Cho 2008;Lee et al 2013;Opere et al 2013). Contrarily, degradation pathways of cyclohexanol and cyclohexanone were described in detail for the bacterial strains Acinetobacter sp.…”
Section: Identification Of a Novel Cyclohexane Monooxygenasementioning
confidence: 98%
“…The ability of B. lentus LP32 to degrade cyclohexane and cyclohexanone is of interest because Bacillus species had rarely been previously reported to play a major role in degradation of alicyclic compound. The only report on cyclohexane degradation by Bacillus till date was that of Lee et al (2013). The authors isolated from loess four strains, Bacillus cereus strain VOC18, Bacillus thuringensis strain VOC 11, B. thuringensis strain VOC13 and Bacillus megaterium strain VOC 03 capable of utilizing or tolerating cyclohexane to varying extents.…”
Section: Biodegradation Of Cyclohexane and Cyclohexanonementioning
confidence: 99%
“…Additionally, the silica content, which relates to the moisture and adsorption properties, was reported to be approximately 45% to 80% (Taylor et al 1983;Muhs 2007). Some studies have reported that loess not only improves indoor air quality, but also has moisture purifying properties (Sun et al 2004;Lee et al 2013).…”
Section: Introductionmentioning
confidence: 99%